DEFINITION, CLASSIFICATION AND CHARACTERISTICS RECEPTIVITY TO THE NEW - Сас, Наталія (SWorldJournal, 2023)
The article reveals the importance of receptivity to the new for the productive modernization of social development and constructive exit from the crisis situation.The result of the theoretical analysis of the scientific works of N. Taleb, I. Prigozhin,